An understanding of Islamic home financing adoption / Mohd Haziq Jalaluddin - Jalaluddin, Mohd Haziq (Faculty of Business and Management, 2015)
The purpose of this study is to determine the consequences of attitude, subjective norm, perceived behavioral control, relative advantage, compatibility, and subjective norm on the adoption of Islamic home financing. An integrative approach is used in this study that combines two theories which are Theory of Planned Behavior (TPB) and Innovation Diffusion Theory (IDT). This study used 120 usable questionnaires that were distributed to the random respondent in selected locations (Melaka and Johor) using snowball sampling method. The data were collected and been analyzed through several analyses such as frequency analysis, descriptive analysis, reliability analysis, correlation analysis, and multiple regression analysis using Statistical package for the social science (SPSS) version 21.0. This study found that integrative approach is valid in the context of Islamic home financing adoption. Therefore, all independent variables were instrumental in determining the adoption of Islamic home financing. However, there are several limitations that researcher faced and limitations for Islamic banks as well. Those limitations and implications are provided for future research and also for Islamic banks itself.